4 - Les communes dans le processus démocratique: la quête difficile d'un pouvoir local effectif en Mauritanie*: by Mouhamadou Abdoul - Mouhamadou Abdoul, (Africa Development, 1996)
Local government in Mauritania has become a reality since 1986, through the experience of the communes. As an entity separate from the central authority, it constitutes a sign of democratization and symbolizes a will for political decentralization set into motion by the Military Committee for National Redemption. However, the communes still remain under the yoke of the central power through hierarchical and supervisory controls, while socially, they are divided along traditional ethnic lines which renders cohabitation between Negro-Africans and Arabo-Berbers extremely difficult. The future and success of local government can only be ensured through the emergence and strengthening of a national sense of identity and by overcoming political and bureaucratic rigidities.